A Chemically Orthogonal Hole Transport Layer for Efficient Colloidal Quantum Dot Solar Cells. Issue 17 (20th March 2020) - Biondi, Margherita; Choi, Min‐Jae; Ouellette, Olivier; Baek, Se‐Woong; Todorović, Petar; Sun, Bin; Lee, Seungjin; Wei, Mingyang; Li, Peicheng; Kirmani, Ahmad R.; Sagar, Laxmi K.; Richter, Lee J.; et al.
Abstract: Colloidal quantum dots (CQDs) are of interest in light of their solution‐processing and bandgap tuning. Advances in the performance of CQD optoelectronic devices require fine control over the properties of each layer in the device materials stack. This is particularly challenging in the present best CQD solar cells, since these employ a p‐type hole‐transport layer (HTL) implemented using 1, 2‐ethanedithiol (EDT) ligand exchange on top of the CQD active layer. It is established that the high reactivity of EDT causes a severe chemical modification to the active layer that deteriorates charge extraction. By combining elemental mapping with the spatial charge collection efficiency in CQD solar cells, the key materials interface dominating the subpar performance of prior CQD PV devices is demonstrated. This motivates to develop a chemically orthogonal HTL that consists of malonic‐acid‐crosslinked CQDs. The new crosslinking strategy preserves the surface chemistry of the active layer beneath, and at the same time provides the needed efficient charge extraction. The new HTL enables a 1.4× increase in charge carrier diffusion length in the active layer; and as a result leads to an improvement in power conversion efficiency to 13.0% compared to EDT standard cells (12.2%). Abstract : A chemically orthogonal hole transport layer for lead sulfide colloidal quantum dot (CQD) solar cells is introduced. By substituting the 1, 2‐ethanedithiol‐treated CQDs with malonic‐acid‐treated CQDs, the surface chemistry of the active layer is preserved. This increases the charge diffusion length by 1.4×, enabling near‐unity charge extraction efficiency at the back electrode, achieving 13.0% efficiency.